La economía política institucional: balance y perspectivas - García Quero, Fernando; López Castellano, Fernando (Iberian Journal of the History of Economic Thought, 2016)
The recent debates on the role of institutions in development are revealing two major theoretical currents: the “New Institutional Economics” and the “Institutional Political Economy”. The New Institutional Economics, whose most notable representatives are Nobel prizes Ronald Coase, Douglass North, Oliver Williamson and Elinor Ostrom, have been thoroughly examined and analyzed. There is however in the Institutional Political Economy (IPE) an important void of academic works that analyze its roots and its main contributions. This paper tries to fill this gap in that literature. The main goal of this paper is twofold: to offer an approximation of IPE and to suggest a classification and an interpretation of institutions, incorporating the perspectives of the main figures in the field.
Keywords: neoinstitucionalism; critical institutionalism; individualizing institutions; contextual institutions; political economy of development.